2022
DOI: 10.2147/copd.s360983
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Validation of COPD Evidenced Care Pathways in Japan, Canada, England, and Germany: Common Barriers to Optimal COPD Care

Abstract: Background Chronic obstructive pulmonary disease (COPD) is a major cause of morbidity and mortality worldwide. A comprehensive and detailed understanding of COPD care pathways from pre-diagnosis to acute care is required to understand the common barriers to optimal COPD care across diverse health systems. Methods Country-specific COPD care pathways were created for four high-income countries using international recommendations and country-specific guidelines, then popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 43 publications
3
11
0
Order By: Relevance
“…Although broadly similar, the theme structure identified in this research differs from the one reported by Meiwald et al (14), where only four HICs were included (Canada, England, Germany and Japan). The key differences are linked to the emergence of two new themes (Themes 6 and 7) that explain how structural issues across healthcare systems affect COPD care.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Although broadly similar, the theme structure identified in this research differs from the one reported by Meiwald et al (14), where only four HICs were included (Canada, England, Germany and Japan). The key differences are linked to the emergence of two new themes (Themes 6 and 7) that explain how structural issues across healthcare systems affect COPD care.…”
Section: Discussionsupporting
confidence: 62%
“…The interview data were analysed using deductive and inductive thematic analysis (25). Transcripts were coded using an existing framework (14). Data within each theme was then coded line by line to create sub-categories (inductive component).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Proper training about rare diseases such as group 1 PH and the use of the appropriate diagnostic procedures are required among health professionals, especially general practitioners, so that patients can be appropriately referred to a specialist/cardiologist for RHC [ 26 ]. Poor general awareness regarding these rare diseases, delays in referrals, misdiagnoses, and poor compliance to the treatment guidelines may lead to worse prognoses [ 27 ]. Our analysis suggests that in the clinical practice of respiratory medicine, which mainly treats CLDs, there are still many barriers to the diagnosis and management of patients with PH in CLD, and there is a need to improve the time to referral, diagnosis, and initiation of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…They align with professional expertise and reiterate issues that challenge care for these conditions outside of BC. Worldwide, there is a need to increase awareness of asthma and COPD as priority chronic respiratory diseases,41–43 increase prevention through mitigation of risk factors, address challenges with asthma and COPD diagnosis,44 45 and better leverage integrated care for effective maintenance 39 40. The features that patients affirmed as valuable could be replicated across VCH for more consistent delivery of quality care and promote equitable health outcomes.…”
Section: Discussionmentioning
confidence: 99%